PENELITIAN DAN PENGUJIAN KARAKTERISTIK AERODINAMIKA BOM LATIH PERCOBAAN BLP-500 DAN BLP 25 - Markis, Yus Kadarusman; Ariwibowo, Agus; Atmadi, Sulistyo (BRIN Publishing, 2004)
Research and aerodynamic testing of BLP-500 and BLP-25 have been conducted in both subsonic and supersonic wind tunnel. Aerodynamic characteristics such as Cl, Cd, and Cm for these types of bomb we obtained. By knowing the aerodynamic characteristics, the stability and trajectory of the bomb can be determined. Both analytical calculation and real tests in the wind tunnel were performed and compared. The results showed that for its static stability, the location of the centre of gravity of BLP-500 and BLP-25 to be less than 115.1 cm and 31.9 cm respectively.